Characterization of the epithelial membrane protein 3 interaction network reveals a potential functional link to mitogenic signal transduction regulation. Issue 2 (20th January 2019) - Christians, Arne; Poisel, Eric; Hartmann, Christian; von Deimling, Andreas; Pusch, Stefan
Abstract : Epithelial Membrane Protein 3 (EMP3), a 4‐transmembrane glycoprotein, first gained attention as a putative tumor suppressor. Accumulating evidence, however, points to a more tumor promotive function of EMP3. The biological function of EMP3 remains largely unclear. To elucidate more of EMP3's interaction network, we performed a Yeast‐Two‐Hybrid (Y2H) screening, followed by validation of candidate interactors by Biomolecular Fluorescence Complementation (BiFC) and Proximity Ligation Assay (PLA). Furthermore, we generated stable EMP3 knockdown cell lines and measured cell proliferation, migration and sensitivity to apoptosis induction as well as the expression and activation levels of important signal pathway components. The Y2H screening yielded 10 novel interactions of EMP3, eight of which could also be detected by BiFC and PLA interaction assays. All newly discovered interaction partners are involved in signaling or trafficking regulation. Most notably, FLOT1 and HTATIP2 have well described roles in the regulation of EGFR signaling. In addition, knockdown of EMP3 resulted in reduced levels of p‐AKT, p‐ERK and p‐EGFR, attenuated cell proliferation and migration and sensitized cells to apoptosis induction by TRAIL and Staurosporine. Based on these observations we hypothesize that EMP3 might be involved in the regulation of receptor‐tyrosine‐kinase mediated mitogenic signaling. Abstract : What's new? The EMP3 glycoprotein appears to be involved in tumor progression in many types of cancer, but its actual function has been unclear. In this study, the authors found that EMP3 interacts with proteins involved in mitogenic signaling. They also found that blocking EMP3 activity reduced tumor‐cell proliferation and migration, and sensitized the cells to apoptosis. These results provide new insight into the role of EMP3 in tumor biology and in signal processing at the cell membrane, which could lead to new therapeutic targets.